2018
DOI: 10.3390/ijms19051423
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 19 (KRT19) has a Role in the Reprogramming of Cancer Stem Cell-Like Cells to Less Aggressive and More Drug-Sensitive Cells

Abstract: Cytokeratin 19 (KRT19) is a cytoplasmic intermediate filament protein, which is responsible for structural rigidity and multipurpose scaffolds. In several cancers, KRT19 is overexpressed and may play a crucial role in tumorigenic transformation. In our previous study, we revealed the role of KRT19 as signaling component which mediated Wnt/NOTCH crosstalk through NUMB transcription in breast cancer. Here, we investigated the function of KRT19 in cancer reprogramming and drug resistance in breast cancer cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 98 publications
1
41
0
Order By: Relevance
“…Moreover, KRT19 + colon cancer stem cells showed high radio-resistance by raising LGR5 + crypt-based columnar cells in the colon and intestines [22]. Recently, we showed that KRT19 has the ability to reprogram breast cancer [23]. Thus, the molecular mechanism underlying the contradictory roles of KRT19 in various cancers needs to be examined to reveal the function of KRT19 in specific cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, KRT19 + colon cancer stem cells showed high radio-resistance by raising LGR5 + crypt-based columnar cells in the colon and intestines [22]. Recently, we showed that KRT19 has the ability to reprogram breast cancer [23]. Thus, the molecular mechanism underlying the contradictory roles of KRT19 in various cancers needs to be examined to reveal the function of KRT19 in specific cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of cytokeratin-19 in TNBC cells prompts proliferation, migration and drug resistance via CXCR4 upregulation. Moreover, low cytokeratin-19 expression in patient samples correlates with poor prognosis [ 140 ]. Another study evaluated the link between cytokeratin-19 expression in cancer cells during the follow-up period after treatment and reached a different conclusion.…”
Section: The Cxcl12/cxcr4-induced Therapy Resistance In Breast Camentioning
confidence: 99%
“…The comparison of the subnetworks of the non-metastatic and the metastatic patients furthermore revealed some patient-specific genes which might give valuable information about specific mechanisms of tumorigenesis and therapeutic vulnerabilities in the respective patient. In general, it seemed that the subnetworks of the non-metastatic patients contained more genes that have been linked to better prognostic outcomes such as JUP, PCBP1 and HMGN2 in GSM615695 (Bailey et al, 2012;Shi et al, 2018;Fan et al, 2018) or RASA1, IL6ST, KRT19 and RPS14 in GSM150990 (Liu et al, 2014;Mathe et al, 2015;Saha et al, 2018;Zhou et al, 2013) while the networks of both metastatic patients harbored genes that are known to be involved in aggressive tumor growth or therapy resistance which might explain the early metastatic spread in these patients. Some examples are CDK1, SFN and XPO1 in GSM519217 (Alexandrou et al, 2019;Neve et al, 2006;Taylor et al, 2019) or CAV1, PTPN11 and FTL in GSM615233 (Qian et al, 2019;Aceto et al, 2012;Chekhun et al, 2013) However, not only the presence of specific genes might be important, but also their overall expression level.…”
Section: Glrp To Deliver Patient-specific Subnetworkmentioning
confidence: 99%